2013
DOI: 10.1590/s1516-35982013001000005
|View full text |Cite
|
Sign up to set email alerts
|

Use of sex-sorted and unsorted frozen/thawed sperm and in vitro fertilization events in bovine oocytes derived from ultrasound-guided aspiration

Abstract: The objective was to investigate the effects of sex-sorting on early fertilization events in ovum pick up (OPU) derived oocytes fertilized in vitro with frozen-thawed sperm at different co-incubation lengths. Eighty-four OPU sessions were carried out in 18 cyclic, dry and non-stimulated Holstein Friesian and German black pied cows. Ovum pick up oocytes were matured in vitro for 24 hours and fertilized with frozen-thawed sex sorted or unsorted sperm from the same ejaculate. Fertilization was achieved by two exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Early embryonic demise after fertilization with SS (x-sorted) both in in vivo and in vitro has been reported (Steele et al, 2020). In contrast, some studies showed that similar cleavage and blastocyst rate for embryos were generated from sexed (x-sorted) and non-sexed sperm (Carvalho et al, 2010;Ruiz López et al, 2003;Xu et al, 2009). Further, overall calving rate following transfer of in vitro produced embryos with non-sorted or x-sorted sperm has been shown to be similar (Carvalho et al, 2010;Rasmussen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Early embryonic demise after fertilization with SS (x-sorted) both in in vivo and in vitro has been reported (Steele et al, 2020). In contrast, some studies showed that similar cleavage and blastocyst rate for embryos were generated from sexed (x-sorted) and non-sexed sperm (Carvalho et al, 2010;Ruiz López et al, 2003;Xu et al, 2009). Further, overall calving rate following transfer of in vitro produced embryos with non-sorted or x-sorted sperm has been shown to be similar (Carvalho et al, 2010;Rasmussen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%